Supercritical CO2 impregnation of PLA/PCL films with natural substances for bacterial growth control in food packaging. (May 2018) - Milovanovic, Stoja; Hollermann, Gesa; Errenst, Cornelia; Pajnik, Jelena; Frerich, Sulamith; Kroll, Stephen; Rezwan, Kurosch; Ivanovic, Jasna
Abstract: Biodegradable polymers with antibacterial properties are highly desirable materials for active food packaging applications. Thymol, a dietary monoterpene phenol with a strong antibacterial activity is abundant in plants belonging to the genus Thymus . This study presents two approaches for supercritical CO2 impregnation of poly(lactic acid)(PLA)/poly(ε-caprolactone)(PCL) blended films to induce antibacterial properties of the material: (i) a batch impregnation process for loading pure thymol, and (ii) an integrated supercritical extraction-impregnation process for isolation of thyme extract and its incorporation into the films, operated in both batch or semi-continuous modes with supercritical solution circulation. The PCL content in films, impregnation time and CO2 flow regime were varied to maximize loading of the films with thymol or thyme extract with preserving films' structure and thermal stability. Representative film samples impregnated with thymol and thyme extract were tested against Gram (−) ( Escherichia coli ) and Gram(+) ( Bacillus subtilis ) model strains, by measuring their metabolic activity and re-cultivation after exposure to the films. The film containing thymol (35.8 wt%) showed a strong antibacterial activity leading to a total reduction of bacterial cell viability. Proposed processes enable fast, controlled and organic solvent-free fabrication of the PLA/PCL films containing natural antibacterial substances at moderately low temperature, with a compact structure and a good thermal stability, for potential use as active food packaging materials. Graphical abstract: Highlights: First study on thymol/thyme extract loading into PLA/PCL films by supercritical CO2 . Batch and semi-continuous impregnation processes were studied. Contact time, %PCL and scCO2 flow regime were varied to enhance the films' loading. Chemical, structural, thermal and antibacterial films' properties were analysed. Thymol (35.8%) loaded PLA-5 film totally reduced E . coli and B . subtilis viability.